ОРГАНІЗАЦІЯ ПІДГОТОВКИ ПЕДАГОГІВ ДО ФАСИЛІТАЦІЙНОЇ ВЗАЄМОДІЇ З УЧНЯМИ (Педагогіка вищої та середньої школи, 2022)
The article introduces the pedagogical education organization model according to the psychological regularities of the personality’s standing mental new features formations.